A Goal Programming Model for Joint Decision Making of Order Allocation, Supplier Selection, and Carrier Selection Considering Corporate Social Responsibility - Rosyidi, Cucuk Nur; Khasanah, Alfia Makrifatul; Laksono, Pringgo Widyo (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
Every company aims to maximize its profit to survive and maintain business growth. However, it has to allocate some of the profit to the community development in the form of corporate social responsibility. Along with the importance of the development of Corporate Social Responsibility (CSR), many companies consider the social effects of their supply chain activities. In this paper, we address a problem determining the optimal order allocation, carrier selection, and the amount of CSR in a single product, multi-suppliers, and multiple periods environment. A goal programming model was developed to solve the problem by considering all-unit quantity discounts, the lateness of deliveries, and rejections. LINGO 18.0 was used to solve the model. The results of optimization show that all the goals are achieved. Based on the sensitivity analysis results, the proposed model is relatively insensitive to the goals of the profit and social value unless at the increases of 24% of both goals. For the goals of defect items and late delivery items, both goals affect the objective function when each goal is decreased. Hence, the decision-maker has to be careful in setting the goals.